Formulation And Evaluation of A Novel Herbal Cream Containing Tretinoin and Pomegranate Extract for The Management of Premature Aging - Rai, Rohit Kumar; Mishra, Ankit; Mishra, J.N (Journal of Neonatal Surgery, 2025)
This study aimed to develop an effective anti-aging cream by combining Tretinoin, a proven retinoid, with pomegranate (Punica granatum) extract known for its antioxidant properties. Creams were prepared using varying concentrations of Tretinoin (0.01%–0.1%) and pomegranate extract (5%–15%) and evaluated for stability, pH, viscosity, skin permeability, and antioxidant activity. In vitro studies assessed collagen synthesis and elastin production. The combination significantly enhanced skin texture, hydration, and antioxidant response, highlighting synergistic anti-aging effects. The results suggest that integrating herbal extracts with Tretinoin offers a promising approach for developing natural and effective anti-aging skincare products